1985
DOI: 10.1136/vr.117.18.459
|View full text |Cite
|
Sign up to set email alerts
|

Disease in a dairy herd associated with the introduction and spread of bovine virus diarrhoea virus

Abstract: In January 1982 an outbreak of diarrhoea among adult dairy cows in a closed herd of approximately 200 milking animals was shown to be caused by the introduction of bovine virus diarrhoea virus (BVDV). Affected animals showed a significant reduction in milk yield. One animal died and four were culled. Eight cows aborted and one weak calf was born. Of 121 calves born that year, 26 died, mostly from pneumonia, but five aged from three weeks to five months had enteric lesions of mucosal disease. Subsequent investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0
5

Year Published

1987
1987
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(53 citation statements)
references
References 0 publications
2
46
0
5
Order By: Relevance
“…Gebe olmayan hayvanlarda ateş, nazal ve oküler akıntı, eroziv stomatitis, löykopeni, ishal ve ineklerde süt veriminde azalma gözlemlenir (24). Gebe hayvanlardaki enfeksiyon tablosu ise biyotipine ve gebeliğin dönemine bağlı olarak persiste enfekte yavru doğumları, anomalili yavru doğumları ve abort oluşumu ile sonuçlanabilmekte-dir (4).…”
Section: Introductionunclassified
“…Gebe olmayan hayvanlarda ateş, nazal ve oküler akıntı, eroziv stomatitis, löykopeni, ishal ve ineklerde süt veriminde azalma gözlemlenir (24). Gebe hayvanlardaki enfeksiyon tablosu ise biyotipine ve gebeliğin dönemine bağlı olarak persiste enfekte yavru doğumları, anomalili yavru doğumları ve abort oluşumu ile sonuçlanabilmekte-dir (4).…”
Section: Introductionunclassified
“…Bovine viral diarrhea virus (BVDV) is a common cattle pathogen with world-wide distribution (Baker, 1987;Houe, 1995). This widespread occurrence makes BVDV infection economically significant (Duffel et al, 1986;Houe, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Also, reduced conception rates in seronegative cows when using BVDVcontaminated semen can be observed (McClurkin et al, 1979;Whitmore et al, 1981). Moreover, animals acutely or persistently infected with BVDV may look healthy, and clinical examination will not provide any suspicion of BVDV infection (Coria and McClurkin, 1978;Cutlip et al, 1980;Barber et al, 1985). Therefore, bulls should be tested, and only virus-negative animals should be introduced into artificial insemination (AI) centers.…”
Section: Introductionmentioning
confidence: 99%
“…l4 However, disease with high mortality rates has also been reported. 4,13,18,30 Cytopathic (CP) and noncytopathic (NCP) BVDV have been recovered from field cases of disease, 3,18 and studies on experimental infections in cattle have demonstrated that both BVDV biotypes are capable of causing mild or severe acute enteritis. 8,9,11,17,20,34 Mixed populations of CP and NCP BVDV have been detected in reference strains.…”
mentioning
confidence: 99%